Didactic games in the performance of a beautiful writing minutes in mother tongue lessons of primary education - Murodullayeva Dilsora Ilhom qizi (Genius Publishing Group, 2023)
In this article, the didactic games for spending moments of beautiful writing in primary class mother tongue lessons: "Who can find the fastest?" game, "Illustrative didactic game", "Thinking game", "Finding the place of the word” It allows you to get information about didactic games such as how to use them, and their importance in forming beautiful writing of students.
Keywords: Didactic games; beautiful writing; correct writing rules; spelling